The Effect of Price, Brand Image and Promotion on Easy Shopping Customer Repurchase Intention Mediated By Customer Satisfaction - Luqmanul Hakim Muthi; Andyan Pradipta Utama (Dinasti Publisher, 2023)
This study aims to analyze the effect of Price, Brand Image, and Promotion on Customer Repurchase Intention on Easy Shopping with Customer Satisfaction as a Mediating Variable. The population are Easy Shopping’s customers and numbers of samples are 170. The analytical method used in this study is the SEM, with data analysis method by Partial Least Square (PLS). Primary data is obtained by distributing Google Form questionnaire to respondents. The results shows that Price, Brand Image, and Promotion have a significant effect on Customer Satisfaction, Customer Satisfaction has a significant effect on Customer Repurchase Intention and can mediate the effect of Price in the partial mediation category, Brand Image, and Promotion in the full mediation category on Customer Repurchase Intention. Research suggestions for Easy Shopping, they can set more reasonable price policy for customers, particularly for member customers who have loyally purchase with certain amounts on Easy Shopping catalog products. Keywords: Price, Brand Image, Promotion, Customer Satisfaction, Customer Repurchase Intention